Management of Metastatic Solid Pseudopapillary Cancer of the Pancreas: A Case Report - Dixon, Matthew (World J Oncol, 2013)
Solid pseudopapillary tumors (SPT) of the pancreas are rare neoplasms predominantly found in females. The tumors are often histologically benign and patient outcomes are correspondingly favorable. This report presents the case of a 21-year-old woman who presented with metachronous metastatic SPT, and details the diagnosis and management of this patient. The patient underwent a distal pancreatectomy for resection of the primary neoplasm with negative margins. A surveillance ultrasound performed at 43 months post-operatively revealed new hepatic lesions; these lesions were surgically resected and pathologically demonstrated to be metastatic SPT of the pancreas. This case report demonstrates the potential for latent metastasis of resected SPT, imaging characteristics of metastatic disease, the need for surveillance of patients following resection of SPT of the pancreas and a review of relevant literature on SPT.